Effectiveness of game board-based learning on improving nutrition knowledge about pedoman gizi seimbang and isi piringku in elementary school students - Rachman, Sonia Aleyda; Lestari, Yanesti Nuravianda (Universitas Nahdlatul Ulama Surabaya, 2025)
This study aimed to evaluate the effectiveness of board games in improving students' knowledge of the Pedoman Gizi Seimbang and Isi Piringku at the elementary school level, compared to the lecture method. This study used a quasi-experimental design with pre-test and post-test involving two groups: an experimental group (n=29) that received the board game intervention, and a control group (n=29) that received the lecture method. The intervention in each group was conducted for 1 week with 45 minutes in one session. The results of the analysis using Wilcoxon test showed that the lecture method significantly improved students' knowledge (p=0.041), while the use of board game did not provide significant improvement (p=0.33). The Mann-Whitney test showed no significant difference between the two methods in increasing students' knowledge (p=0.36). In conclusion, the lecture method is more effective in the short term, while the board game requires a longer duration to produce a significant impact.